2023
DOI: 10.1186/s13287-023-03287-7
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal/stem cell (MSC)-derived exosomes in clinical trials

Abstract: Mesenchymal stromal/stem cells (MSCs) are widely utilized in cell therapy because of their robust immunomodulatory and regenerative properties. Their paracrine activity is one of the most important features that contribute to their efficacy. Recently, it has been demonstrated that the production of various factors via extracellular vesicles, especially exosomes, governs the principal efficacy of MSCs after infusion in experimental models. Compared to MSCs themselves, MSC-derived exosomes (MSC-Exos) have provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(37 citation statements)
references
References 97 publications
0
26
0
Order By: Relevance
“…Having established a biomimetic cardiac fibrosis-on-a-chip, we next expected to utilize this chip for therapeutic exploration. Stem cell therapy has gained wide attention in the field of heart regeneration. ,, Particularly, MSC-Exo, which resolves intrinsic limitations of direct stem cell transplantation including immunogenicity and tumorigenesis risk, has been investigated for postmyocardial infarction healing. Here we investigated whether MSC-Exo treatment could improve the TGF-β1-induced phenotype in our biomimetic chip. First, MSC-Exos were isolated by using a series of ultracentrifugations.…”
Section: Resultsmentioning
confidence: 99%
“…Having established a biomimetic cardiac fibrosis-on-a-chip, we next expected to utilize this chip for therapeutic exploration. Stem cell therapy has gained wide attention in the field of heart regeneration. ,, Particularly, MSC-Exo, which resolves intrinsic limitations of direct stem cell transplantation including immunogenicity and tumorigenesis risk, has been investigated for postmyocardial infarction healing. Here we investigated whether MSC-Exo treatment could improve the TGF-β1-induced phenotype in our biomimetic chip. First, MSC-Exos were isolated by using a series of ultracentrifugations.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, an increasing number of studies have shown that stem cell extracellular vesicles exhibit similar functions without these shortcomings 17,29 . Therefore, stem cell extracellular vesicle‐based therapy is of great importance in tissue engineering and translational medicine 30–32 …”
Section: Discussionmentioning
confidence: 99%
“…HEK293T cells were obtained from ATCC (Manassas, VA) and maintained in the same media as the hTERT-MSCs between passage 2 and 30. The HEK cells were plated at 7.7E4 cells/cm 2 the day before transfection. For each transfection, 4.878μg of IRF1 lentiviral plasmid, 1.463μg of pMD2.G and 3.659μg of psPAX2 (Addgene, Watertown, MA) were transfected using JetPRIME (Polyplus, Illkirch, France).…”
Section: Methodsmentioning
confidence: 99%
“…Mesenchymal Stem/Stromal Cells (MSCs) are widely recognized for their potential for treating diverse classes of human diseases and disorders. 1 The efficacy of MSCs or their cell-free products 2,3 has been studied in hundreds of clinical trials 4 across multiple settings spanning neurodegenerative disorders, 5 inflammatory bowel disease, 6 cardiac diseases, 7 COVID-19, 8 and others. This broad potential stems from the ability of MSCs to simultaneously express and secrete a spectrum of different pleiotropic immunomodulatory and regenerative chemokines, cytokines, growth factors, metabolites, and vesicles.…”
Section: Introductionmentioning
confidence: 99%